Pengaruh CR, EPS, NPM dan ROA Terhadap Return Saham pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2014-2018 - Ranisa Dwi Octaviana; Siti Ruhana Dara (STREAMING, 2022)
Current Ratio (CR), Earning Per Share (EPS), Net Profit Margin (NPM), and Return On Assets (ROA) on stock return of in food and beverage companies in Indonesia Stock Exchange (IDX) for the 2014-2018 period, Partial. The sample in this study is the food and beverage subsector company proposed on the Indonesia Stock Exchange for the 2014-2018 period. Sampling in this study using purposive sampling technique, and obtained a sample of 18 companies. The method of data analysis uses multiple regression. The results of the study show that the partial NPM and ROA variables affect stock returns, and the CR and EPS does not affect stock returns. The results of the coefficient of determination (Adjusted R-squared) obtained a value of 0.159, this value explains the variables CR, EPS, NPM, and ROA has effect on stock return on food and beverage company listed in the Indonesia Stock Exchange during the period 2014-2018 amounted 15.9%.